Hypothalamic paraventricular nucleus neurons activated by estrogen GPER1 receptors promote anti-inflammation effects in the early stage of colitis. (15th November 2019) - Jiang, Tao; Wang, Ruoxi; Yin, Wen; Zhou, Yuxi; Kong, Dexu; Xu, Saihong; Gao, Po; Yu, Weifeng; Jiao, Yingfu; Wen, Daxiang
Abstract: The hypothalamus–pituitary–adrenal (HPA) axis is known to mediate gut–brain interaction, and the pathological inflammatory process in the intestine can induce HPA axis involved 'fight or flight' response to suppress or facilitate intestinal inflammation. Hypothalamic paraventricular nucleus (PVN) neurons are responsible for controlling the HPA axis activity, but their exact role in modulating intestinal inflammation remains unclear. In this study, we used the dextran sulfate sodium (DSS)-induced mice colitis model, gene editing, and RNA interference to determine the effects of PVN neurons on intestinal inflammation. We found that at the early stage (third day) after DSS treatment, there was a mild inflammation in the colorectal area and an increased neuron activation in the PVN but not in the adjacent area. At the same time, ~80% of activated PVN neurons also expressed novel estrogen GPER1 receptor. The colitis noticeably worsened in GPER1-knockout mice and local PVN GPER1-knockdown mice. These results indicated that PVN GPER1 positive neurons potentially have a protective function during the early stages of DSS-induced colitis, and this may be a mechanism by which the central nervous system attempts to suppress intestinal inflammation to achieve self-protection.